Characteristics of atherosclerotic plaque and the thickness of the carotid artery intima-media complex in patients with rheumatoid arthritis - Aleksić, Ivana; Stojanović, Sonja; Stamenković, Bojana; Kostić, Svetlana; Stojanović, Milovan (Vojnosanitetski pregled, 2023)
Background/Aim. Rheumatoid arthritis (RA) represents an independent risk factor for the development of cardio-vascular (CV) disease (CVD). Early detection of atheroscle-rotic changes is of tremendous importance in the preven-tion of CV events. An increase in the carotid artery intima-media thickness (cIMT) is considered a sensitive marker of early subclinical atherosclerosis. The aim of our investiga-tion was to assess the cIMT, the number and type of carotid plaques (CPs), and the severity of carotid artery stenosis in RA patients. Furthermore, we investigated the correlation between all the above-mentioned parameters and disease duration and activity. Methods. The research included 92 participants, of which 58 were patients with RA, and the remaining 34 participants were healthy individuals (control group). In patients with RA, clinical examination and labor-atory findings were used for assessing disease activity. All participants underwent a color Doppler ultrasound exami-nation of the carotid arteries with a linear probe in order to assess cIMT, the number and type of CPs, as well as the se-verity of stenotic lesions. Results. The mean cIMT in RA patients was statistically significantly higher compared to the control group (0.8 ± 0.2 mm vs. 0.7 ± 0.2 mm; p < 0.01). CPs were found in 34 out of 58 RA patients (58.6%) and 4 out of 34 (11.8%) participants in the control group (p < 0.001). The number of CPs per patient was signifi-cantly higher in the RA group compared to the control group (1.4 ± 0.9 vs. 0.2 ± 0.4; p < 0.001). The cIMT, the presence and number of CPs, and the severity of carotid artery stenosis were not statistically significantly related to disease activity. There was a statistically significant direct correlation between the duration of RA and the percent-age of carotid arterial stenosis (r = 0.320, p = 0.034). Con-clusion. The cIMT and the presence and number of CPs per patient were significantly higher in RA patients. More-over, there was a positive correlation between RA disease duration and the severity of carotid artery stenosis. This study showed that RA represents an independent risk fac-tor for an increase in cIMT and the development of sub-clinical atherosclerosis.